Структура і послідовність формування мотиваційного механізму активізації інноваційної діяльності машинобудівного підприємства - Разінькова, М.Ю. (Економіка промисловості, 2015)
Актуалізовано потребу стимулювання активності людських ресурсів з метою забезпечення інноваційного розвитку підприємств у сучасних умовах господарювання. Систематизовано методологічний апарат, обґрунтовано структуру та послідовність створення мотиваційного механізму активізації інноваційної діяльності машинобудівного підприємства. Визначено перелік суб’єктивних та організаційних чинників формування даного механізму. Актуализирована потребность стимулирования активности человеческих ресурсов с целью обеспечения инновационного развития предприятий в современных условиях хозяйствования. Систематизирован методологический аппарат, обоснована структура и последовательность создания мотивационного механизма активизации инновационной деятельности машиностроительного предприятия. Определен перечень субъективных и организационных факторов формирования данного механизма. The article actualizes the need to stimulate the activity of human resources in order to provide innovative development of companies in the current economic conditions. The methodological apparatus is systematized, the structure and sequence of the motivational mechanism to activate innovation activity of engineering enterprise is grounded, which is a combination of motives of employees’ conscious attitude to their own actions, behavior, internal grounds of behavior, the state of readiness for certain actions which are formed under the influence of motive forming influences, i.e. factors of different nature which result in motive forming influence. Important components of the mechanism should be: incentives; values; ideals; value orientations. The priority for constructing the mechanism under consideration is the need to ensure: creativity (generation of new solutions); performance (efficiency and utility); handling (in relation to resources and reserves, planning, evaluation of actions, stimulation of motivation). The list of subjective and organizational factors in the formation of the mechanism is identified, its components are characterized and the direction of their interaction is shown; the importance of considering the needs and capabilities, values and ideals of the staff are highlighted, which should be a factor of increasing the effectiveness of the objectives implementation of innovative activity motivation of the enterprise as a whole.